1966
DOI: 10.3133/pp524e
|View full text |Cite
|
Sign up to set email alerts
|

Tectonics of the Keweenawan basin, western Lake Superior region

Abstract: The subsurface structure of the western Lake Superior region iJ3 analyzed by combining information on surface geology with fl,eromagnetic, gravity, and paleomagnetic data. Surface attitudes and the map pattern suggest that the upper Keweenawan sedimentary rocks (Bayfield and Oronto Groups) have the general form of a lens, thickening southeastward from a featheredge close to the Minnesota shore of Lake Superior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…3b-3d). Gravity data (White, 1966), however, do not support the concept of a collapsed feeder under Lake Superior for the Keweenawan layered intrusions. Plate tectonic concepts have provided a new perspective from which to view the structural relations of the Keweenawan layered intrusions.…”
Section: Layered Gabbroic and Associated Granitic Plutonic Rocksmentioning
confidence: 54%
See 1 more Smart Citation
“…3b-3d). Gravity data (White, 1966), however, do not support the concept of a collapsed feeder under Lake Superior for the Keweenawan layered intrusions. Plate tectonic concepts have provided a new perspective from which to view the structural relations of the Keweenawan layered intrusions.…”
Section: Layered Gabbroic and Associated Granitic Plutonic Rocksmentioning
confidence: 54%
“…8), Cooper and others (1981) have accumulated evidence for the existence of a northeast-and northwest-trending fault system. This system may be interpreted to represent a series of rift White, 1966). Western part of Mellen Complex mapped by Leighton (1954) is included in the Mineral Lake intrusion.…”
Section: Layered Gabbroic and Associated Granitic Plutonic Rocksmentioning
confidence: 99%
“…These intense anomalies are not well understood, although Hinze et al (1982) and Dickas (1986c) suggest that they might be produced by relatively thick sections of low-density Bayfield Group sedimentary rocks, thinning of the rift's dense volcanic sequence, or low-density sources beneath the rift basin. White (1966b) suggested that the southern (Bayfield Peninsula) negative anomaly is produced by a ridge of pre-Keweenawan basement rocks above which the rift's volcanic rocks are relatively thin or absent. Until this study, however, no quantitative models have been proposed.…”
Section: Geophysical Elements and Methodologymentioning
confidence: 98%
“…Reverse faults (Fig. 2) thrust older volcanic rocks and Oronto Group strata over younger Bayfield Group rocks and delineate the margins of uplifted volcanicrooted horsts (Thiel, 1956;White, 1966b;Dickas, 1986b), such as the St. Croix Horst of Minnesota and Wisconsin (SCH, Fig. 2).…”
Section: Geologic Elementsmentioning
confidence: 99%
“…The Keweenawan Supergroup (1.1 Ga) in the Lake Superior Basin (Figure 1) consists of a thick sequence of volcanic and sedimentary rocks which filled a portion of the Mideontinent rift system during Proterozoic time (White 1966, Chase and Gilmer, 1973, Daniels 1982, Cannon et al 1989. The stratigraphic section near White Pine consists of a basal unit of 5-13 km of mafic to intermediate flows of the Portage Lake Volcanics and the Porcupine Volcanics (Cannon and Nicholson 1992).…”
Section: Geological Setting and Units Analyzedmentioning
confidence: 99%